High Emission Scenario Substantially Damages China's Photovoltaic Potential. Issue 20 (18th October 2022) - Lu, Ning; Yao, Ling; Qin, Jun; Yang, Kun; Wild, Martin; Jiang, Hou
Abstract: Quantifying future changes in solar photovoltaic (PV) potential is of great significance for energy planning and policy making to achieve carbon neutrality. To constrain the uncertainties of applying directly Coupled Model Intercomparison Project Phase 6 (CMIP6) projections to such quantification, we construct the performance‐weighted CMIP6 solar irradiance and air temperature data, and then assess the future changes in China's PV potential and accompanying economic benefits under three typical climate change scenarios. We find that the high emission scenario will substantially damage China's PV potential, resulting in a reduction of 314 TWh/year in electricity generation by the planned installed capacity in 2100, with a corresponding loss of US $25 billion/year. However, the low emission scenario will enhance the PV potential, yielding an additional electricity generation of 226 TWh/year and a corresponding bonus of US $18 billion/year in 2100. China's commitment to carbon neutrality will lead to low‐carbon emissions, which brings great economic rewards to its PV industry. Plain Language Summary: Quantifying the impact of climate change on future solar photovoltaic (PV) potential is important for energy planning and policy development in the context of the carbon neutrality. However, directly applying Coupled Model Intercomparison Project Phase 6 (CMIP6) projections to this quantification leads to large uncertainties. To this end, we reconstruct the future solar irradiance and air temperature data by weighting the CMIP6 projections according to their performance in reproducing the historical changes. Afterward, we assess the future changes in China's PV potential and the associated economic impacts under three typical climate change scenarios. We find that China's PV potential would significantly decrease under high emissions scenario, equal to an electricity generation of 314 TWh/year at planned installed capacity in 2100 and economic loss of about $25 billion/year. In contrast, PV potential would increase under low emission scenario, resulting in an additional electricity of 226 TWh/year and economic benefits of $18 billion/year. China is striving to achieve low emission development with the carbon neutrality commitment, from which the Chinese PV industry will reap huge economic rewards. Key Points: Synthesis of Coupled Model Intercomparison Project Phase 6 projections by Bayesian linear regression reduces the uncertainties of solar irradiance and air temperature China's future capacity factor will continuously decrease (increase) to about 0.141 (0.152) by 2100 under high (low) emission scenario High emissions will result in a reduction of 314 TWh/year in electricity generation, with a corresponding loss of US $25 billion/year